Haematolymphoid Tumours Karyotypes: A Moroccan Population Retrospective Study from 1992 to 2021 - Charlène Soro, Somda Georgina; Benchikh, Sara; Charoute, Hicham; El Hamouchi, Adil; Aboulfaraj, Jamila; Razoki, Lunda; Zarouf, Latifa; Elbakay, Chadli; Rifai, Lala Laila; Saile, Rachid; Lebrazi, Halima; Nassereddine, Sanaa (Asian Pacific Journal of Cancer Biology, 2024)
Background: Haematolymphoid tumours are a heterogeneous group of pathologies involving cells of the haematopoietic lineage. Data reported here focus on the results of a descriptive, general, exclusive epidemiological study from a Moroccan population. Objective: Our research aimed to study the distribution of Haematolymphoid tumours in the regional context in Casablanca. Method: We focused on malignancies diagnosed between January 1992 and December 2021 at the Cytogenetics Department of the Pasteur institute of Morocco. Conventional karyotype analysis was performed on bone marrow samples from patients aged between 1 and 95 years and collected data were analyzed to perform statistical analyzes using SPSS20.0 software. Results: Of the karyotypes investigated 69.8% (1118/1601) were positive for haematolymphoid tumours. The mean age at diagnosis was 42.68 ± 18.20 years. The most frequent pathologies were myeloid neoplasms, with chronic myeloid leukaemia (CML) in first place at 69.8% (780/1118), followed by acute leukaemias (ALL, AML and ALAL) at 21.4% and myelodysplastic neoplasm (MDS) at 5.5%. The most recurrent clonal abnormalities were translocations t (9;22) with 74.2% in CML cases. Deletions 12.5% and additions 8% were found in all diseases with mainly trisomy’s 8 and 21 in AML and MDS and deletions in AML and ALAL. An association was also found in 12 cases of AML between t (8;21) translocation and sexual chromosome deletion (X and Y). The proportion of karyotype’s complexity (9.9%) seems to increase with ages. Conclusions: Haematolymphoid tumours occur at an earlier age in this cohort. Leukaemia represents the most frequent pathologies with a preponderance of chronic diseases, mainly affecting adults.